Radioactive! : how Irène Curie and Lise Meitner revolutionized science and changed the world - Conkling, Winifred (Algonquin Young Readers, 2018)
Describes how Irène Curie, the daughter of Marie Curie, discovered artificial radioactivity in 1934 and earned a Nobel Prize along with her husband. Her work set the stage for physicist Lise Meitner to unlock the secret of nuclear fission four years later. Discusses how Curie and Meitner were discriminated against for their gender, yet their accomplishments were crucial in the development of nuclear energy and ultimately, the nuclear bomb. Includes over fifty period photographs and sidebars.